POLEX-SOUTH DATA, PART 3 : RADIATION DATA AT MIZUHO STATION, ANTARCTICA IN 1980 - ISHIKAWA, Nobuyoshi; KOBAYASHI, Shun'ichi; OHATA, Tetsuo; KAWAGUCHI, Sadao (National Institute of Polar Research, 1982)
P(論文) departmental bulletin paper